2005
DOI: 10.1097/01.ftd.0000159784.25872.f6
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Mycophenolic Acid in Kidney Transplant Pediatric and Adolescent Patients

Abstract: Current data on mycophenolate mofetil (MMF) suggest that there is a pharmacokinetic/pharmacodynamic relationship between the mycophenolic acid (MPA) area under the curve (AUC) during treatment and both the risk of acute rejection and the occurrence of side effects. The aim of this study was to characterize the population pharmacokinetics of MPA in kidney transplant patients between the ages of 2 and 21 years and to propose a limited sampling strategy to estimate individual MPA AUCs. Forty-one patients received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
123
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(136 citation statements)
references
References 45 publications
12
123
1
Order By: Relevance
“…Blood samples were collected in tubes containing ethylenediaminetetraacetate (EDTA), immediately centrifuged, and kept frozen (−20°C) until centralized analysis. Plasma MPA concentrations were determined by high-performance liquid chromatography (HPLC) with ultraviolet detection using method previously used in our laboratory [23]. PK parameters were normally distributed (tested by Kolmogorov-Smirnov test) and are expressed as mean ± SD.…”
Section: Mmf Pharmacokineticmentioning
confidence: 99%
“…Blood samples were collected in tubes containing ethylenediaminetetraacetate (EDTA), immediately centrifuged, and kept frozen (−20°C) until centralized analysis. Plasma MPA concentrations were determined by high-performance liquid chromatography (HPLC) with ultraviolet detection using method previously used in our laboratory [23]. PK parameters were normally distributed (tested by Kolmogorov-Smirnov test) and are expressed as mean ± SD.…”
Section: Mmf Pharmacokineticmentioning
confidence: 99%
“…The current success of organ transplantation is largely correlated to advances in immunosuppressive therapy and very few allografts are now lost as a result of acute rejection. Mycophenolate mofetil (MMF) has become in recent years a more widely prescribed drug, used for maintenance immunosuppressive therapy both in adult [1] and pediatric renal-transplant recipients [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, pharmacokinetics studies in adults and children revealed substantial inter-and intra-individual variability in pharmacokinetics parameters, and significant drug interactions [3,[10][11][12][13]. Therefore, both in adults and children, TDM of MPA is now an important tool in transplantation to optimize therapy [13][14][15].…”
Section: Introductionmentioning
confidence: 99%